(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Academic writing proficiency is a crucial skill for success in higher education and professional contexts, yet many learners encounter persistent difficulties in specific areas such as grammar accuracy, coherence, lexical diversity, and argument development. This study investigates the effectiveness of targeted writing exercises designed to address these particular weaknesses among intermediate-level university students. Through diagnostic assessment, participants were grouped according to their primary writing challenges and engaged in customized practice activities over a six-week intervention period. Pre- and post-test analyses revealed statistically significant improvements in all groups, demonstrating that focused and deliberate writing exercises can effectively enhance the specific components of academic writing. These findings underscore the importance of personalized instruction tailored to learner needs and contribute to the growing body of research supporting targeted pedagogical approaches in writing education. The study highlights practical implications for educators seeking to improve academic writing outcomes through strategic intervention.